2006
DOI: 10.1111/j.1365-2141.2006.06279.x
|View full text |Cite
|
Sign up to set email alerts
|

A detailed study of time‐dependent changes in human red blood cells: from reticulocyte maturation to erythrocyte senescence

Abstract: SummaryThe use of microfabrication technology in the study of biological systems continues to grow rapidly in both prevalence and ascendancy. Customised microdevices that provide superior results than traditional macroscopic methods can be designed in order to investigate specific cell types and cellular processes. This study showed the benefit of this approach in precisely characterising the progressive losses of surface area and haemoglobin (Hb) content by the human red blood cell (RBC), from newborn reticul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
98
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 37 publications
(52 reference statements)
11
98
1
Order By: Relevance
“…10 Mature reticulocytes released from BM undergo final remodeling after release, resulting in a 10%-14% membrane loss in the first 48 hours. 29 Consistent with this, the circumference of cultured reticulocytes lacking staining for either LAMP1 or CD63 (30.92 Ϯ 2.31 m, n ϭ 8) was 10% less than those staining positive for either marker (33.96 Ϯ 2.23 m, n ϭ 9).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…10 Mature reticulocytes released from BM undergo final remodeling after release, resulting in a 10%-14% membrane loss in the first 48 hours. 29 Consistent with this, the circumference of cultured reticulocytes lacking staining for either LAMP1 or CD63 (30.92 Ϯ 2.31 m, n ϭ 8) was 10% less than those staining positive for either marker (33.96 Ϯ 2.23 m, n ϭ 9).…”
Section: Discussionsupporting
confidence: 64%
“…10 Mature reticulocytes released from BM undergo final remodeling after release, resulting in a 10%-14% membrane loss in the first 48 hours. 29 Consistent with this, the circumference of cultured reticulocytes lacking staining for either LAMP1 or CD63 (30.92 Ϯ 2.31 m, n ϭ 8) was 10% less than those staining positive for either marker (33.96 Ϯ 2.23 m, n ϭ 9).To determine the source of GPA in GPA-positive cytosolic vesicles, R2 reticulocytes were incubated at 37°C in the presence of anti-GPA, and the appearance of GPA-positive vesicles observed over time ( Figure 6A). The results clearly showed that GPA derives from the plasma membrane.…”
mentioning
confidence: 99%
“…Erythroblastic islands were first observed in bone marrow, although they are also present in the splenic red pulp and in the fetal liver (Chasis and Mohandas, 2008;Manwani and Bieker, 2008). These islands consist of a central macrophage that extends cytoplasmic protrusions to a ring of 5-30 surrounding erythroid cells encompassing proerythroblast to reticulocyte stages (Gifford et al, 2006). Extensive macrophage-erythroblast and erythroblast-erythroblast adhesive interactions are necessary for a thriving definitive erythropoietic community.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has become possible to identify and characterize very young (hours or days old) circulating RBCs (reticulocytes) (2). RBCs undergo a rapid reduction in volume and hemoglobin in the few days after release from the bone marrow (3). This rapid phase is followed by a much longer period of slower reduction (4-7) during which volume and hemoglobin are coregulated (8) (Fig.…”
mentioning
confidence: 99%